2004
DOI: 10.1080/16501960410015371
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the concepts contained in outcome measures of clinical trials on musculoskeletal disorders and chronic widespread pain using the international classification of functioning, disability and health as a reference

Abstract: The ICF provides a useful reference to identify and quantify the concepts contained in outcome assessment used in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 18 publications
1
49
0
4
Order By: Relevance
“…Compared with earlier reviews, [17][18][19][20][21] we found low relative frequencies of the linked ICF categories. One explanation is that these other reviews included clinical trials only, whereas we selected a much broader range of studies.…”
Section: Discussionmentioning
confidence: 45%
“…Compared with earlier reviews, [17][18][19][20][21] we found low relative frequencies of the linked ICF categories. One explanation is that these other reviews included clinical trials only, whereas we selected a much broader range of studies.…”
Section: Discussionmentioning
confidence: 45%
“…Since "decision making skills," "setting limits," "prioritizing," and "focusing" are defined as important problems in a considerable number of patients with chronic pain [66][67], it is not a surprising finding that in some patients, it turned out to be impossible to obtain COPM priorities and scores at all or that stated priorities became irrelevant during the course of the program.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar de outros instrumentos 16,17,18 usados para avaliar a funcionalidade de pessoas com lombalgia abordarem alguns desses aspectos 19,20 , o core set da CIF para lombalgia traz a vantagem de documentar a melhora ou deterioração neste componente, seja em função das funções e estruturas corpóreas ou pela modulação pelos fatores ambientais. Por exemplo, restaurar o desempenho do paciente para o trabalho remunerado (d845, d850 e d859) pode ser obtido por meio do fortalecimento muscular do paciente (b730) ou com alterações nos instrumentos de trabalho (e135).…”
Section: Categoriaunclassified